Znaczenie energii odnawialnej w polityce eurośródziemnomorskiej - uwarunkowania i perspektywy rozwoju - Diawoł-Sitko, Anna (Rocznik Integracji Europejskiej, 2015)
The paper presents the conditions and prospects for the development of Euro-Mediterranean cooperation in the field of renewable energy sources (RES). The first part characterises the objectives of the European Union and member states in the field of renewable energy, the second concerns the energy situation in Mediterranean countries, in particular the renewable energy sector, the third presents renewable energy projects implemented within the framework of the Euro-Mediterranean initiative, and part four shows the problems related to the implementation of projects in the renewable energy sector, both in Mediterranean countries as well as within the framework of Euro-Mediterranean programmes. Europe’s energy strategy is closely linked to energy security and diversification of the energy sector by increasing production and consumption of energy from renewable sources. This goal is to be achieved by both domestic production of RES and through trade. Due to their geographical proximity, co-developed institutions and potential, Mediterranean countries are a priority in this strategy. The development of the renewable energy sector in Mediterranean countries may also generate indirect positive effects for Europe and stimulate enhanced Euro-Mediterranean coop- eration in other socio-economic fields.